Toll-Like Receptor 4–Induced IL-22 Accelerates Kidney Regeneration - Kulkarni, Onkar P. (American Society of Nephrology, 2014)
AKI involves early Toll-like receptor (TLR)–driven immunopathology, and resolution of inflammation is needed for rapid regeneration of injured tubule cells. Notably, activation of TLRs also has been implicated in epithelial repair. We hypothesized that TLR signaling drives tubule regeneration after acute injury through the induction of certain ILs. Systematic screening in vitro identified IL-22 as a candidate proregeneratory factor in primary tubular cell recovery, and IL-22 deficiency or IL-22 blockade impaired post-ischemic tubular recovery after AKI in mice. Interstitial mononuclear cells, such as dendritic cells and macrophages, were the predominant source of IL-22 secretion, whereas IL-22 receptor was expressed by tubular epithelial cells exclusively. Depleting IL-22–producing cells during the healing phase impaired epithelial recovery, which could be rescued entirely by reconstituting mice with IL-22. In vitro, necrotic tubular cells and oxidative stress induced IL-22 secretion selectively through TLR4. Although TLR4 blockade during the early injury phase prevented tubular necrosis and AKI, TLR4 blockade during the healing phase suppressed IL-22 production and impaired kidney regeneration. Taken together, these results suggest that necrotic cell–derived TLR4 agonists activate intrarenal mononuclear cells to secrete IL-22, which accelerates tubular regeneration and recovery in AKI.